Kualitas Kimia Kompos Hasil Biokonversi Berbagai Jenis Limbah Organik Menggunakan Larva Black Soldier Fly dan EM-4: Kualitas Kimia Kompos Hasil Biokonversi Berbagai Jenis Limbah Organik Menggunakan Larva Black Soldier Fly dan EM-4 - Deni Pratama; Rion Apriyadi; Rahmat Lingga; Meri Rahmawati (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2022)
Waste is a major problem that is often faced by Indonesian people. The existence of waste that has not been handled properly will have a negative impact on the quality of the community's environment. Waste handling with the bioconversion method with the help of Black soldier Fly (BSF) larvae and EM-4 bio-activator can minimize waste capacity and be useful for the community. This study aims to compare the ability between bioconversion agent and quality of various types of organic waste that use for bioconversion. The research was conducted in January – August 2022 at Experimental dan Research Garden (KP2) Universitas Bangka Belitung and Laboratory of Indonesian Center for Biodiversity and Biotechnology. This study used a factorial randomized block design (RAKF) with 2 factors. The first factor were bioconversion agents consist of 3 levels, P0 (control), P1 (EM-4 activator) (15 ml), P2 (Black Soldier Fly) (5 grams/bio-pond). The second factor were different kind of organic waste materials consists of 3 levels, L1 (pineapple peel waste), L2 (orange peel waste), L3 (bagasse). The results showed that BSF larvae had a potential as bioconversion agent and its ability close to EM-4. Generally, application of bioconversion agent increased the quality of compost compare to without application of bioconversion agent.  Application of bioconversion agent combined with pineapple peel waste had quality close to standards from Ministry of Agriculture No. 261, 2019.